Conservation science: a 20‐year report card. Issue 9 (1st November 2006) - Lawler, Joshua J.; Aukema, Juliann E.; Grant, Jacqualine B.; Halpern, Benjamin S.; Kareiva, Peter; Nelson, Cara R.; Ohleth, Kris; Olden, Julian D.; Schlaepfer, Martin A.; Silliman, Brian R.; Zaradic, Patricia
Abstract : We conducted an intensive review of conservation science to find out whether the field has tracked priorities over the past 20 years. A total of 628 papers from the literature, for the years 1984, 1994, and 2004, were surveyed. For each paper, we recorded where conservation research was done and what was studied. We found geographic gaps in conservation research, with marine, tundra, and desert biomes being studied less than other systems. We also found taxonomic gaps, with amphibians being understudied as compared to other, less threatened, taxonomic groups. Finally, we discovered that studies of invasive species are still lacking, despite the magnitude of the threat they pose to global biodiversity. Although there was a weak trend towards filling these gaps between 1984 and 2004, progress has been slow. To be more effective, the research community must quickly redirect research to better match conservation priorities.